HUBUNGAN IBU PEROKOK PASIF SEBAGAI FAKTOR LINGKUNGAN TERHADAP KEJADIAN CELAH BIBIR DENGAN ATAU TANPA CELAH PALATUM NONSINDROMIK (Pada Pasien RSI Sultan Agung Semarang Bulan Juni 2012) - Beti Ratnasari; Rizki Amalina; Yayun Siti Rochmah; Arlina Nurhapsari (Jurnal Medali, 2013)
Nonsyndromic cleft lip with or wihout cleft palate (CL±CP) is a congenital defect caused by genetic and environmental factors. One of the its environmental factors is passive smoking mother. The increasing risk of CL±CP in passive smoking mothers occurs due to the fetal hypoxia caused by carbon monoxide and nicotine in cigarette smoke. The aim of this study is to determine the relationship of passive smoking mothers as environmental factor towards the incidence of nonsyndromic CL±CP in patients of Sultan Agung Islamic Hospital Semarang June 2012.This study used cross sectional method. The samples were 16 CL±CP patients at Sultan Agung Islamic Hospital Semarang June 2012 with their mothers who had fulfilled exclusion and inclusion criteria stated in the questionnaire and 16 control subjects. The motherswere qualified as passive smokers if they met all requirements. The data analysis involved Chi-square test as descriptiveand hypothesis test.The analysis results showed significant relationship (p<0,05) with prevalence ratio (RP)=2,647 and confidence interval (CI) 95%=1,083-6,469. Twelve out of sixteen CB±CP patients’ mothers were passive smokers.  In conclusion, there is a relationship between passive smoking mothers as environmental factor towards the incidence of nonsyndromic CL±CP in patients of Sultan Agung Islamic Hospital Semarang June 2012.Keywords: passive smoking mothers, cleft lip, cleft lip with cleft palate, nonsyndromic, carbon monoxide, nicotine, hypoxia